Nontargeted Metabolomics (Reverse phase) - Analysis of Foods Standard Operating Procedure (SOP) - Odenkirk, Melanie T (2025)
This Standard Operating Procedure (SOP) describes a nontargeted metabolomics workflow for comprehensive small molecule profiling in foods using solid-phase extraction and reverse phase liquid chromatography-mass spectrometry. The protocol involves extracting lyophilized food with aqueous methanol, followed by protein precipitation and SPE cleanup to remove lipids and matrix interferents. Samples are spiked with internal retention time standards, dried, reconstituted, and analyzed by high-resolution MS, with reference samples as quality controls for comparative profiling across diverse food matrices. For unresolved issues, users are encouraged to seek additional assistance via ptfionboarding@gmail.com.